2014
DOI: 10.4067/s0717-92002014000300007
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the environmental quality of a protected riparian forest in Southern Brazil

Abstract: SUMMARYEnvironmental Protection Areas (EPA) are of extreme importance for species conservation and establishment. We investigated different areas of riparian forests in the Environmental Protection Area of Ibirapuitã, southern Brazil. We analyzed the environmental quality of these areas by studying the lichen community and using the index of atmospheric purity (IAP) with the environmental classification factor (ECF) as the correction factor. The lichen community was analyzed in 12 riparian forest stands locate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 25 publications
0
2
0
3
Order By: Relevance
“…Studies with vascular epiphytes in the HBSR area have verified changes in richness and diversity of the riparian forest sites in different matrices and have emphasized the importance of their conservation and preservation (Rocha-Uriartt et al 2016). In this study, we found that the preservation actions associated with agropastoral practices were decisive for the conservation of habitats, such as in the S4 forest site of the rural-urban matrix, in which rare species were found, including Herpothallon pustulatum (crustose) and the genera Ricasolia and Sticta, which are known to occur in more preserved environments (Käffer & Martins 2014;López et al 2016;Lehnen et al 2017).…”
Section: Discussionmentioning
confidence: 77%
“…Studies with vascular epiphytes in the HBSR area have verified changes in richness and diversity of the riparian forest sites in different matrices and have emphasized the importance of their conservation and preservation (Rocha-Uriartt et al 2016). In this study, we found that the preservation actions associated with agropastoral practices were decisive for the conservation of habitats, such as in the S4 forest site of the rural-urban matrix, in which rare species were found, including Herpothallon pustulatum (crustose) and the genera Ricasolia and Sticta, which are known to occur in more preserved environments (Käffer & Martins 2014;López et al 2016;Lehnen et al 2017).…”
Section: Discussionmentioning
confidence: 77%
“…En relación con los resultados obtenidos tras la aplicación del IPA, se demuestra que la estación E7 ubicada en el centro del pasivo ambiental minero Santo Toribio, posee el valor más bajo del IPA con 12,15 representando así, la presencia de mayores niveles de contaminación atmosférica en comparación a las demás estaciones de muestreo. El resultado obtenido, es explicado por la mayor cercanía de este punto con los desechos mineros presentes (material de desbroce, relaves mineros y drenaje ácido de mina), los cuales fueron producidos por la antigua actividad de la empresa Santo Toribio S.A. Por otro lado, la estación control establecida como muestra blanco, obtuvo el mayor valor de IPA con 31,50 representando de esta manera la zona con menor grado de contaminación y por ende la más favorable para el desarrollo de las especies, esta diferencia de valores de IPA entre áreas de estudio, estaría en concordancia con trabajos llevados a cabo por autores como Crespo et al (1981), Canseco et al (2006), Lijteroff et al (2009), Käffer et al (2011) y Käffer & Martins (2014), los cuales muestran dentro de sus resultados menores valores de IPA en zonas con presencia de perturbación ambiental y mayores valores de IPA en zonas menos perturbadas.…”
Section: Discussionunclassified
“…A presença de liquens fruticosos está associada a locais mais úmidos (Giordani et al 2013, Käffer & Martins 2014, Matos et al 2015. Segundo MartinsMazzitelli et al (2006), os liquens fruticosos são os mais sensíveis à poluição atmosférica, sendo os primeiros a desaparecerem em áreas muito degradadas, podendo-se sugerir que no ambiente rural amostrado as condições microclimáticas associado às características ambientais da região estavam mais favoráveis para a ocorrência destes espécimes quando comparado à área urbana analisada.…”
Section: Discussionunclassified
“…Nyl na área II (rural) se destaca neste estudo. Esta espécie é característica de ambientes mais preservados e úmidos (Käffer & Martins 2014), o que confere uma melhor condição ambiental a esta área. Este gênero tem sido citado como indicador de ecossistemas florestais preservados, com alta continuidade ecológica (Campbell & Fredeen 2004, Liira & Sepp 2009, Gjerde et al 2012.…”
Section: Discussionunclassified